John Fiske's Semiotic Analysis: Representation of Social Criticism in Pretty Boys - Tasya Arlina; Reni Nuraeni (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to analyze the representation of social criticism in the film Pretty Boys using John Fiske's semiotic analysis. In this study, the researcher used a qualitative research method with a descriptive type of research to examine a social critique that occurred in the film "Pretty Boys." In contrast, the approach used was John Fiske's semiotic approach which was used to investigate the level of reality, the level of representation, and the level of ideology. Based on the analysis, it is known that at the reality level, nine television codes represent social criticism through four scenes analyzed by the researchers, namely the display code, dress code, and makeup code—media owner. At the representation level, five television codes represent social criticism through four scenes analyzed by the researcher showing the camera code the shooting technique used is close up to show Bayu's gesture when giving an example to appear as a kemayu man to Rahmat and Anugrah, medium close up shows the player's expression, the medium shot shows the atmosphere captured by the camera and the extended photo shows the player's clothing, makeup, words, and gestures clearly. At the ideological level, it describes the existence of an ideology of capitalism which shows that media ownership is concerned with economic profit compared to the interests of the audience, with Karl Max's critical theory as a supporter and the commodification that occurs behind a media, the author concludes that there is a social criticism that arises in the Pretty Boys film.